New perspectives on the structure of transnational criminal justice - Christensen, Mikkel Jarle; Boister, Neil (Brill research perspectives. Transnational crime., 2018)
National criminal justice systems are slowly integrating in an effort to combat cross border criminality. 'New perspectives on the structure of transnational criminal justice' provides a forum for critical perspectives on this evolving system, with the goal of testing and challenging conceptions of transnational criminal law. Collectively, the papers in this special issue investigate the main symbolic and material characteristics of this space of justice, how it is organized and what dynamics shape its functionality and impact.